The Effect of Supervisory Performance on The Quality of Mathematics Education In Grade II Students of EBC Turiscai - Celestino Caldeira; Antonio Guterres (Green Publisher Indonesia, 2024)
Improving the performance of supervisors and the quality of student education has a positive relationship because a maximum and good learning style will provide good quality education. The hypothesis of the supervisor performance variable (X) on the quality of education (Y) of students in Ensino Basico 3o Ciclo Turiscai shows that there is a positive and significant influence individually because the ttable > is 7,937> 2,000 then Ha is accepted. This means that better supervisor performance (X) will provide higher quality education for students at Ensino Basico 3o Ciclo Turiscai. From the results of the calculation of a simple regression correlation analysis, it shows that the coefficient (r) of 0.722 or 72.2% means that the supervisory performance variable (X) has a fairly close relationship or has a strong enough correlation with the variable Education quality (Y) in Ensino Basico 3o Ciclo Turiscai and the coefficient of determination (r2) of 0.521 or 52.1% means that the contribution or contribution of supervisor performance (X) is given to the variable Education quality (Y) of 0.521 or 52.1% while The remaining 47.9% was influenced by other factors. Based on the calculation results with a simple linear regression analysis model, the value is obtained that the supervisory performance variable (X) shows a unidirectional or positive regression coefficient value of 0.628 against the education quality variable (Y). This can be interpreted that the performance of supervisors (X) affects the quality of education (Y) by 0.628 or 62.8% in Ensino Basico 3o Ciclo Turiscai.